Recovering Post-withdrawal Costs: Indemnity Clause, Bailment and Unjust Enrichment - SEE, Alvin W. L. (Institutional Knowledge at Singapore Management University, 2012)
The Supreme Court decision inENE 1 Kos Ltd v Petroleo Brasileiro SA Petrobras (The Kos) raised two issues of general importance: one on the construction of an indemnity clause in a time charter, and another on the nature of a gratuitous bailee's right to charge the bailor for the cost of taking care of the latter's goods.